Prussian white material and preparation method thereof, positive plate, battery and electric equipment

By covering the pure manganese-based Prussian white shell with nickel-doped manganese element on the pure manganese core surface of the Prussian white material, the structural degradation problem caused by the ginger Taylor effect during the charging and discharging process is solved, and high capacity and excellent cyclic stability are achieved. sex.

CN119447271AActive Publication Date: 2025-02-14NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510019349.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-02-14
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

Prussian white materials rich in manganese are prone to trigger the ginger Taylor effect during the charge and discharge process, resulting in material particles corrosion and dissolution, intergranular cracks, continuous increase in interface impedance, severe deterioration of the body phase structure, and poor circulation stability.

Method used

The surface of the pure manganese-based Prussian white material is coated with a manganese-based Prussian white material doped with nickel elements, which stabilizes the crystal structure of the material, thereby inhibiting the occurrence of the Jiang Taylor phenomenon and enhancing the overall stability of the material.

Benefits of technology

By covering the shell of nickel, the material has high capacity and excellent cycle stability, effectively inhibiting the occurrence of the ginger Taylor effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447271A_ABST
    Figure CN119447271A_ABST
Patent Text Reader

Abstract

The invention provides a Prussian white material and a preparation method thereof, a positive plate, a battery and electric equipment. The Prussian white material comprises an inner core and a first shell coating the surface of the inner core, the composition of the inner core is NaxMn [Fe (CN) 6] y.alphaH2O, x is greater than or equal to 1 and less than or equal to 1.8, y is greater than or equal to 0.9 and less than or equal to 0.99, and alpha is greater than or equal to 1 and less than or equal to 3; the composition of the first shell is NaaMnbNi1-b [Fe (CN) 6] c.betaH2O, 1.2 < = a < = 1.8, 0.8 < = b < = 0.995, 0.8 < = c < = 0.99, and 0.5 < = beta < = 3. The surface of the pure manganese-based Prussian white material is coated with the manganese-based Prussian white material shell doped with the nickel element, so that the crystal structure of the material can be stabilized, the ginger Taylor phenomenon is inhibited, the overall stability of the material is enhanced, and the material has high capacity and excellent cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries and relates to a Prussian white material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. Background Art

[0002] Prussian white material has a three-dimensional skeleton structure that is conducive to the migration of large-sized sodium ions and a high specific capacity, making it an ideal positive electrode material for sodium ion batteries. However, manganese-rich Prussian white material is prone to induce the Jan-Taylor effect during the charge and discharge process, resulting in corrosion and dissolution of material particles, generation of intergranular cracks, continuous increase in interface impedance, and severe degradation of the bulk structure, and has poor cycle stability. Therefore, how to improve the cycle stability of Prussian white material is a technical problem that needs to be solved urgently in this field. Summary of the invention

[0003] The present invention provides a Prussian white material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. The Prussian white material of the present invention is formed by coating a manganese-based Prussian white material shell doped with nickel elements on the surface of a pure manganese-based Prussian white material, so that the crystal structure of the material can be stabilized to inhibit the occurrence of the Jan-Taylor phenomenon, enhance the overall stability of the material, and enable the material to have both high capacity and excellent cycle stability.

[0004] A first aspect of the present invention provides a Prussian white material, comprising a core and a first shell coated on the surface of the core;

[0005] The composition of the core is Na x Mn[Fe(CN)6] y αH2O, where 1≤x≤1.8, 0.9≤y≤0.99, 0.5≤α≤3;

[0006] The composition of the first shell is Na a Mn b Ni 1-b [Fe(CN)6] c βH2O, where 1.2≤a≤1.8, 0.8≤b≤0.99, 0.8≤c≤0.995, 0.5≤β≤3.

[0007] The Prussian white material as described above, wherein the particle size of the inner core is 1-6 μm; and / or the thickness of the first outer shell is 1-2 μm.

[0008] The Prussian white material as described above, wherein the surface of the first shell is further covered with a second shell, and the composition of the second shell is Na m Ni[Fe(CN)6] n γH2O, where 0.5≤m≤1.9, 0.9≤n≤0.99, 0.05≤γ≤1.5.

[0009] The Prussian white material as described above, wherein the thickness of the second shell is 50-100 nm.

[0010] The Prussian white material as described above, wherein the outer surface of the Prussian white material is a carbonized layer.

[0011] The Prussian white material as described above, wherein the thickness of the carbonized layer is 2-15 nm.

[0012] The Prussian white material as described above, wherein the Prussian white material comprises the first shell and a carbonized layer located on the surface of the first shell, and the carbonized layer is formed by in-situ carbonization of the first shell;

[0013] Alternatively, the Prussian white material includes the second shell and a carbonized layer located on a surface of the second shell, wherein the carbonized layer is formed by in-situ carbonizing the second shell.

[0014] The Prussian white material as described above, wherein the in-situ carbonization comprises: forced air drying at 60-100°C for 4-24 hours, followed by vacuum drying at 120-200°C for 16-24 hours, and finally vacuum calcination at 205-240°C for 0.5-5 hours.

[0015] The Prussian white material as described above, wherein the Ni content in the Prussian white material is 2000-10000 ppm, and the Mn content is 15-30 wt%.

[0016] The Prussian white material as described above, wherein the Prussian white material satisfies at least one of the following conditions:

[0017] (1) Specific surface area ≥ 4.5m 2 / g;

[0018] (2) Sodium ion diffusion coefficient ≥ 1.14×10 -10 ;

[0019] (3) D50 particle size is 2~10μm;

[0020] (4) The difference in mass content between carbon and nitrogen is 0.5%~9.5%;

[0021] (5) Water content ≤1200ppm.

[0022] A second aspect of the present invention provides a method for preparing the Prussian white material as described above, comprising the following steps:

[0023] 1) adding a mixed solution of a soluble divalent manganese salt and sodium ferrocyanide to a mixed solution of a soluble sodium salt and sodium ferrocyanide at a rate of 1-2 L / h to perform a first coprecipitation reaction to obtain a first solution including a core;

[0024] 2) adding a mixed solution of a soluble divalent manganese salt, a soluble divalent nickel salt and sodium ferrocyanide to the first solution to perform a second coprecipitation reaction to form a first shell on the surface of the inner core to obtain the Prussian white material.

[0025] The preparation method as described above, wherein, after the first shell is formed on the surface of the inner core, it further includes adding an aqueous solution of a soluble divalent nickel salt to the reaction solution to perform a third coprecipitation reaction to form a second shell to obtain the Prussian white material.

[0026] The preparation method as described above, wherein, after forming the first shell or forming the second shell, it also includes blowing drying the material at 60-100°C for 4-24 hours, then vacuum drying at 120-200°C for 16-24 hours, and finally vacuum calcining at 205-240°C for 0.5-5 hours to form a carbonized layer on the surface of the Prussian white material.

[0027] A third aspect of the present invention provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer, wherein the positive electrode active material layer comprises the Prussian white material provided by the first aspect of the present invention.

[0028] A fourth aspect of the present invention provides a battery, comprising the positive electrode sheet provided by the third aspect of the present invention.

[0029] A fifth aspect of the present invention provides an electrical device, comprising the battery provided by the fourth aspect of the present invention.

[0030] The implementation of the present invention has at least the following advantages:

[0031] The Prussian white material provided by the present invention can stabilize the crystal structure of the Prussian white material by coating the surface of the pure manganese Prussian white core with a manganese-based Prussian white shell doped with nickel elements, thereby inhibiting the occurrence of the Jan-Taylor phenomenon, enhancing the overall stability of the material, and enabling the material to have both high capacity and excellent cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0033] Figure 1 This is a comparison diagram of the appearance of the Prussian white materials of Examples 1 to 6;

[0034] Figure 2The SEM comparison images of the Prussian white materials of Examples 1 to 6;

[0035] Figure 3 This is an EDS comparison chart of the Prussian white material of Example 5;

[0036] Figure 4 This is a comparison diagram of impedance curves of button-type batteries assembled with Prussian white materials according to Example 2, Example 3, Example 5, and Example 6;

[0037] Figure 5 This is a comparison diagram of the XRD characteristic curves before and after the Prussian white material is coated on the shell of Example 1;

[0038] Figure 6 This is a comparison chart of the rate performance of button cells assembled with the Prussian white materials of Examples 1 to 6;

[0039] Figure 7 This is the SEM image of the Prussian white material of Example 11. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below in combination with the embodiments of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0041] Prussian white material has a three-dimensional skeleton structure that is conducive to the migration of large-sized sodium ions and a high specific capacity, making it an ideal positive electrode material for sodium ion batteries. 2+ / Mn 3+ The valence change plays an important role in improving the charge and discharge capacity of Prussian white materials. Prussian white materials with high manganese content are conducive to obtaining high capacity of the material, while too high manganese content can easily cause the Prussian white material to induce the Jan-Taylor effect during the charge and discharge process, resulting in part of the manganese element being Mn 2+ dissolves in the electrolyte in the form of ions, resulting in unstable material structure and poor cycle performance.

[0042] Based on this, the first aspect of the present invention provides a Prussian white material, comprising a core and a first shell coated on the surface of the core;

[0043] The composition of the core is Na x Mn[Fe(CN)6] y αH2O, where 1≤x≤1.8, 0.9≤y≤0.99, 0.5≤α≤3;

[0044] The composition of the first shell is Na a Mn b Ni 1-b [Fe(CN)6] c βH2O, where 1.2≤a≤1.8, 0.8≤b≤0.995, 0.8≤c≤0.99, 0.5≤β≤3.

[0045] The present invention coats a first shell of nickel-manganese-based Prussian white (Mn-NiHCF) on the surface of a pure manganese Prussian white (MnHCF) core, wherein the first shell is doped with nickel elements in the manganese-based Prussian white material, which can stabilize the crystal structure of the Prussian white material and thus inhibit the occurrence of the Jan-Taylor phenomenon, enhance the overall stability of the material, and enable the material to have both high capacity and excellent cycle stability.

[0046] Smaller material particle size means larger specific surface area, and can also improve the reaction kinetics of the material, allowing sodium ions to diffuse to the active sites of the material faster. However, if the particle size is too small, it is easy to agglomerate and cause the structure of the material to undergo a phase change, which is not conducive to the structural stability of the material. Based on this, the particle size of the core is controlled to be 1~6μm. Exemplarily, the particle size of the core can be 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, or a range consisting of any two of them.

[0047] Although a larger thickness of the first shell can better enhance the cycle stability of the material, it will also significantly affect the capacity value of the material. In order to achieve a better balance between the cycle stability and capacity of the material, the thickness of the first shell is controlled to be 1-2 μm. Exemplarily, the thickness of the first shell is 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2 μm, or a range consisting of any two of these values.

[0048] In some specific embodiments, the first shell surface further includes a second shell, and the composition of the second shell is Na m Ni[Fe(CN)6] n γH2O, where 0.5≤m≤1.9, 0.9≤n≤0.99, 0.05≤γ≤1.5.

[0049] The second shell is pure nickel Prussian white material (Ni-HCF), which has strong inertness and can further improve the cycle stability of the material.

[0050] It is understandable that the thickness of the second shell should not be too thick, otherwise it will have a significant adverse effect on the capacity of the material. Based on this, the thickness of the second shell is controlled to be 50-100 nm. Exemplarily, the thickness of the second shell can be 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, or a range consisting of any two of these values.

[0051] In some specific embodiments, the outer surface of the Prussian white material is a carbonized layer.

[0052] The carbonized layer on the outer surface is rich in carbon elements, which can provide additional conductive networks and sodium ion diffusion paths, promote the penetration of electrolytes, and alleviate the problems of poor material conductivity and reduced capacity caused by inert Ni doping. At the same time, it can also increase the specific surface area of ​​the material and reduce the impedance value of the material.

[0053] Too large a thickness of the carbonized layer will also affect the capacity of the material. Based on this, the thickness of the carbonized layer is controlled to be 2 to 15 nm so that the material has both high capacity, specific surface area and conductivity. Exemplarily, the thickness of the carbonized layer can be 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm or a range consisting of any two of these values.

[0054] When the Prussian white material of the present invention includes only the core and the first shell, the carbonized layer is located on the surface of the first shell and can be formed by in-situ carbonizing the first shell.

[0055] When the Prussian white material of the present invention includes a core, a first shell and a second shell, the carbonized layer is located on the surface of the second shell and can be formed by in-situ carbonizing the second shell.

[0056] The carbonized layer formed by in-situ carbonization of the first shell or the second shell has high uniformity and density, and almost no single carbon particle is formed, thereby avoiding the formation of a conductive dead zone.

[0057] Furthermore, the in-situ carbonization includes: forced air drying at 60-100°C for 4-24 hours, followed by vacuum drying at 120-200°C for 16-24 hours, and finally vacuum calcination at 205-240°C for 0.5-5 hours.

[0058] The above carbonization process is carried out in stages, wherein the temperature difference of each stage is controlled to be 40~100°C, and each stage adopts stage airflow protection drying, and the gases used include but are not limited to air, nitrogen, argon, etc., and the gas flow rate can be controlled at 2~15L / h.

[0059] Blast drying at 60~100℃ can remove the adsorbed water on the surface of the material, followed by vacuum drying at 120℃~200℃ to remove the interstitial water in the material, and finally high-temperature treatment under an inert gas flow above 200℃ can remove the crystallized water inside the material and carbonize the surface of the material to form a carbonized layer in situ. By performing multiple stages of heating under different atmospheres during the drying process, while forming a surface carbonized layer in situ, the oxidative decomposition of the surface material can be avoided, and most of the adsorbed water and interstitial water in the material can be removed, reducing the water content of the material.

[0060] In addition, the nickel element of the first shell and the second shell can make the material have good structural stability, and the subsequent in-situ carbonization treatment at high temperature can still prevent the decomposition of the material.

[0061] In some preferred embodiments, the Ni content in the Prussian white material is 2000-10000 ppm, and the Mn content is 15-30 wt %.

[0062] By controlling the Ni content and Mn content in the overall Prussian white material within the above range, a certain amount of Ni element can be doped into the material to maintain the structural stability of the material, and a sufficient amount of Mn content can be maintained to keep the material at a high capacity.

[0063] Exemplarily, the Ni content in the Prussian white material can be 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm, 6000ppm, 7000ppm, 8000ppm, 9000ppm, 10000ppm or a range consisting of any two of the above, and the Mn content can be 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, or a range consisting of any two of the above.

[0064] In some specific embodiments, the Prussian white material of the present invention satisfies at least one of the following conditions:

[0065] (1) Specific surface area ≥ 4.5m 2 / g;

[0066] (2) Sodium ion diffusion coefficient ≥ 1.14×10 -10 ;

[0067] (3) D50 particle size is 2~10μm;

[0068] (4) The difference in mass content between carbon and nitrogen is 0.5%~9.5%;

[0069] (5) Water content ≤1200ppm.

[0070] When the specific surface area of ​​the material is ≥4.5m 2 / g, indicating that the material has more active sites, which is more conducive to the material's capacity. Coating and controlling particle size are important means to achieve high specific surface area. Experimental research has found that the formation of a carbonized layer on the outer surface can significantly increase the specific surface area of ​​the material and prevent the material from agglomerating, which is the preferred means to achieve high surface area of ​​the material.

[0071] The sodium ion diffusion coefficient refers to the diffusion rate of sodium ions in Prussian white materials, which can be obtained by electrochemical impedance spectroscopy (EIS) or cyclic voltammetry (CV) testing. The sodium ion diffusion coefficient of the controlled material is ≥1.14×10 -10 , which enables sodium ions to move quickly inside the material, helping to achieve fast charging and discharging. Controlling the particle size of the material, introducing other elements to change the crystal structure of the material, and coating the surface of the material with a conductive layer are all important means to increase the sodium ion diffusion coefficient of the material. Research has found that by providing a carbonized layer on the outer surface of the material, the sodium ion diffusion coefficient of the material can be increased by an order of magnitude, while the material can maintain high capacity and good structural stability, which is the preferred means to achieve a high sodium ion diffusion coefficient of the material.

[0072] The D50 particle size of the material is controlled within the range of 2-10 μm, preferably 5-7 μm, which is beneficial for subsequent slurry coating of electrodes. In addition, the D50 particle size has good consistency within the above range, avoiding local stress concentration and volume change, which helps to extend the cycle life of the battery.

[0073] Specifically, the D50 particle size of the material can be controlled within the above range by regulating the aging time of the material during the preparation process.

[0074] Exemplarily, the D50 particle size of the material may be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or a range consisting of any two of the above values.

[0075] When the material surface is carbonized, carbon is deposited on the surface of the material, while nitrogen is converted into gas and released, increasing the difference in mass content of carbon and nitrogen in the material as a whole. Studies have found that controlling the mass content difference of carbon and nitrogen to 0.5%~9.5% can ensure that the surface of the material is in a slightly carbonized state, which can avoid the reduction of material capacity caused by excessive carbonization.

[0076] Illustratively, the difference in mass content of carbon and nitrogen elements in the material can be 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5% or a range consisting of any two of the above values.

[0077] During the synthesis process of Prussian white material, it is inevitable that some crystal water will occupy the active sites, which reduces the specific capacity and structural stability of the material. At the same time, the material itself is very easy to absorb water. The water content can be as high as 100000ppm when placed in daily storage. It is easy to escape and react with the electrolyte during the battery cycle, which leads to the collapse of the material structure and the failure of the electrolyte. The surface moisture of the material is easy to react with the surface material at high temperature to form a gray oxide layer, which affects the electrochemical properties of the material. The present invention can effectively remove the adsorbed water and interstitial water in the material through a staged airflow drying process, so that the water content of the whole material (the sum of adsorbed water, interstitial water and crystallization water) is ≤1200ppm.

[0078] A second aspect of the present invention provides a method for preparing the Prussian white material as described above, the method comprising the following steps:

[0079] 1) adding a mixed solution of a soluble divalent manganese salt and sodium ferrocyanide to a mixed solution of a soluble sodium salt and sodium ferrocyanide at a rate of 1 to 2 L / h to perform a first coprecipitation reaction to obtain a first solution including a core; illustratively, the addition rate may be 1 L / h, 1.1 L / h, 1.2 L / h, 1.3 L / h, 1.4 L / h, 1.5 L / h, 1.6 L / h, 1.7 L / h, 1.8 L / h, 1.9 L / h, 2 L / h or a range consisting of any two of the above values.

[0080] 2) Adding a mixed solution of a soluble divalent manganese salt, a soluble divalent nickel salt and sodium ferrocyanide to the first solution, performing a second coprecipitation reaction, forming a first shell on the surface of the inner core, and obtaining a Prussian white material.

[0081] Specifically, the soluble divalent manganese salt, soluble sodium salt, and soluble divalent nickel salt include but are not limited to chlorides, sulfates, nitrates, acetates, etc. Specifically, the soluble divalent manganese salt may be one or more of manganese sulfate, manganese nitrate, manganese acetate, and manganese chloride; the soluble sodium salt may be one or more of sodium chloride, sodium sulfate, sodium nitrate, and sodium acetate; the soluble divalent nickel salt may be one or more of nickel sulfate, nickel nitrate, nickel acetate, and nickel chloride.

[0082] In some specific embodiments, the conditions of the first coprecipitation reaction are: 60-80° C., 100-300 rpm, and 6-8 hours.

[0083] After the first coprecipitation reaction is completed, the reaction system can be heated to 50-90° C. and aged for a certain period of time to control the nucleation particle size of the inner core.

[0084] In some specific embodiments, the conditions of the second coprecipitation reaction are: 20-40° C., 100-300 rpm, and 4-6 hours.

[0085] Furthermore, after the first shell is formed on the surface of the inner core, the process further includes adding an aqueous solution of a soluble divalent nickel salt to the reaction solution to perform a third coprecipitation reaction so as to form a second shell on the surface of the first shell.

[0086] In some specific embodiments, the conditions of the third coprecipitation reaction are: 20-40° C., 100-300 rpm, and reaction time of 6-8 h.

[0087] After the third coprecipitation reaction is completed, the material can be kept warm, stirred and aged for a certain period of time so as to control the overall particle size of the material.

[0088] Specifically, the concentration of the solution added in the first coprecipitation reaction, the second coprecipitation reaction, and the third coprecipitation reaction can be controlled to control the particle size of the inner core and the thickness of the first outer shell and the second outer shell.

[0089] It should be noted that the first coprecipitation reaction, the second coprecipitation reaction, the third coprecipitation reaction and the aging process need to be carried out under an inert gas protection atmosphere, which can avoid unnecessary oxidation and hydration, help to improve the purity of the material and reduce its water content.

[0090] Furthermore, after forming the first shell or the second shell, the material is also subjected to air drying at 60-100°C for 4-24 hours, followed by vacuum drying at 120-200°C for 16-24 hours, and finally vacuum calcining at 205-240°C for 0.5-5 hours, so as to form a carbonized layer on the surface of the Prussian white material while removing adsorbed water and interstitial water in the material synthesis process, thereby reducing the water content of the material.

[0091] A third aspect of the present invention provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer, wherein the positive electrode active material layer comprises the Prussian white material provided by the first aspect of the present invention.

[0092] Since the positive electrode sheet of the present invention includes the Prussian white material having both high capacity and structural stability, the positive electrode sheet can also have both high capacity and good structural stability during application.

[0093] The present invention does not particularly limit the positional relationship between the positive electrode current collector and the positive electrode active material layer. The positive electrode active material can be directly disposed on one or both sides of the positive electrode current collector, or other functional layers or primer layers can be included between the positive electrode current collector and the positive electrode active material layer.

[0094] In addition to the above-mentioned positive electrode materials, the positive electrode active material layer of the present invention also includes components such as a conductive agent and a binder. Among them, the conductive agent and the binder can be selected from materials commonly used in the art. Specifically, the conductive agent can be selected from one or more of conductive carbon black, acetylene black, Ketjen black, and carbon nanofibers, and the binder can be selected from one or more of PVDF, sodium carboxymethyl cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, and styrene-butadiene rubber.

[0095] The present invention does not specifically limit the preparation method of the positive electrode sheet, and the positive electrode sheet can be prepared by a conventional preparation method in the art. For example, the Prussian white material, the conductive agent and the binder are dispersed in a solvent in proportion to obtain a slurry, and then the slurry is coated on at least one surface of the positive electrode current collector, and the positive electrode sheet can be obtained after drying, slitting and rolling.

[0096] A fourth aspect of the present invention provides a battery, comprising the positive electrode sheet provided by the third aspect of the present invention.

[0097] Since the battery includes the above positive electrode sheet with both high capacity and structural stability, the battery also has high capacity performance, cycle stability and rate performance during the charge and discharge process.

[0098] In addition to the above-mentioned positive electrode sheet, the battery of the present invention also includes conventional battery components such as a negative electrode sheet, an electrolyte and a separator. Among them, the composition of the negative electrode sheet, the electrolyte and the separator can refer to the conventional composition in the art and will not be repeated here.

[0099] The battery of the present invention can be prepared by referring to conventional methods in the art. For example, the positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence, and then a battery cell is obtained through a lamination or winding process, and then the battery of the present invention is obtained through baking, liquid injection, formation, packaging and other processes.

[0100] The fifth aspect of the present invention provides an electric device, comprising the battery provided in the fourth aspect of the present invention. The present invention does not specifically limit the type of electric device, and it can be any electric device including the battery, including but not limited to mobile phones, portable devices, laptop computers, electric bicycles, electric cars, electric toys, energy storage devices, lighting equipment, cameras, etc.

[0101] The Prussian white material and its application provided by the present invention are further described in detail below in conjunction with specific embodiments.

[0102] Example 1

[0103] This embodiment provides a Prussian white material, and the preparation method thereof comprises the following steps:

[0104] 1) Under nitrogen atmosphere, 15 L of a mixed solution of 1 mol / L manganese sulfate solution and 0.5 mol / L sodium ferrocyanide was pumped into 10 L of a base solution containing 0.1 mol / L sodium sulfate and 0.002 mol / L sodium ferrocyanide at a rate of 1.875 L / h, and stirred at a constant temperature of 25 °C for 8 h;

[0105] The temperature was then raised to 55°C and the first aging was carried out at a stirring speed of 300 rpm for 8 hours. After the temperature was lowered to 25°C, 2.5 L of a mixed solution of manganese sulfate (concentration 0.9 mol / L) and nickel sulfate (concentration 0.45 mol / L) with a concentration ratio of 2:1 and 4 L of 0.413 mol / L sodium ferrocyanide solution were pumped into the aged solution again, and stirring was continued during the process.

[0106] Then, 2.15 L of 0.028 mol / L nickel sulfate solution was additionally pumped into the solution, and a second aging was performed at a constant temperature of 25° C. and a stirring speed of 200 rpm for 8 h, so that the D50 particle size of the particles grew to 5 μm, thereby obtaining a Prussian white material precursor solution.

[0107] 2) filtering the Prussian white material precursor solution to obtain a Prussian white material precursor, drying the precursor at 80° C. for 24 h, then vacuum drying the precursor at 180° C. for 24 h, and finally raising the temperature to 240° C. for vacuum calcination for 0.5 h to obtain a Prussian white material;

[0108] During the vacuum drying process, nitrogen was added every 30 min and the vacuum was drawn again.

[0109] The core of Prussian white material is composed of Na 1.543 Mn[Fe(CN)6] 0.907 1.57H2O, the composition of the first shell is Na 1.687 Mn 0.991 Ni 0.009 [Fe(CN)6] 0.922 1.46H2O, the composition of the second shell is Na 1.831 Ni[Fe(CN)6] 0.94 1.33H2O.

[0110] Example 2

[0111] This embodiment provides a Prussian white material, and its preparation method is basically the same as that of embodiment 1, except that step 2) is as follows:

[0112] The Prussian white material precursor solution was filtered to obtain the Prussian white material precursor, the precursor was blown dried at 100°C for 4 hours, then vacuum dried at 200°C for 24 hours, and finally the temperature was increased to 240°C and vacuum calcined for 1 hour to obtain the Prussian white material; during the vacuum drying process, nitrogen was supplemented every 30 minutes and then vacuum dried again.

[0113] Example 3

[0114] This embodiment provides a Prussian white material, and its preparation method is basically the same as that of embodiment 1, except that step 2) is as follows:

[0115] The Prussian white material precursor solution was filtered to obtain the Prussian white material precursor, the precursor was blown dried at 60°C for 24 hours, then vacuum dried at 120°C for 24 hours, and finally the temperature was increased to 240°C and vacuum calcined for 2.5 hours to obtain the Prussian white material; during the vacuum drying process, nitrogen was added every 30 minutes and then vacuumed again.

[0116] Example 4

[0117] This embodiment provides a Prussian white material, and its preparation method is basically the same as that of embodiment 1, except that step 2) is as follows:

[0118] The Prussian white material precursor solution was filtered to obtain the Prussian white material precursor, the precursor was blown dried at 80°C for 24 hours, then vacuum dried at 200°C for 16 hours, and finally the temperature was increased to 205°C and vacuum calcined for 5 hours to obtain the Prussian white material; during the vacuum drying process, nitrogen was supplemented every 30 minutes and then vacuumed again.

[0119] Example 5

[0120] This embodiment provides a Prussian white material, and its preparation method is basically the same as that of embodiment 1, except that step 2) is as follows:

[0121] The Prussian white material precursor solution was filtered to obtain a Prussian white material precursor, and the precursor was dried in an air environment at 80° C. for 24 hours to obtain a Prussian white material.

[0122] Example 6

[0123] This embodiment provides a Prussian white material, and its preparation method is basically the same as that of embodiment 1, except that step 2) is as follows:

[0124] The Prussian white material precursor solution was filtered to obtain a Prussian white material precursor, and the precursor was dried under a vacuum environment at 170° C. for 24 hours to obtain a Prussian white material.

[0125] Example 7

[0126] This embodiment provides a Prussian white material, and its preparation method is basically the same as that of Example 1, except that: step 1) omits the additional pumping of 2.15 L of 0.028 mol / L nickel sulfate solution, and step 2) omits the vacuum calcination at 240° C. for 0.5 h.

[0127] Example 8

[0128] This embodiment provides a Prussian white material, and the preparation method thereof is substantially the same as that of Embodiment 1, except that step 2) omits the vacuum calcination at 240° C. for 0.5 h.

[0129] Example 9

[0130] This embodiment provides a Prussian white material, and the preparation method thereof is substantially the same as that of Embodiment 1, except that in step 2), the material is calcined in vacuum at 240° C. for 24 h.

[0131] Example 10

[0132] This embodiment provides a Prussian white material, and the preparation method thereof is substantially the same as that of Embodiment 1, except that the additional pumping of 2.15 L of 0.028 mol / L nickel sulfate solution is omitted in step 1).

[0133] Embodiment 11

[0134] This embodiment provides a Prussian white material, and its preparation method is basically the same as that of Example 1, except that step 2) is as follows: filtering the Prussian white material precursor solution to obtain a Prussian white material precursor, and ball-milling and mixing Ketjen black (0.5% of the mass of Prussian white) and the Prussian white material precursor at 1000 rpm to obtain a Prussian white material.

[0135] Example 12

[0136] This embodiment provides a Prussian white material, and its preparation method is basically the same as that of Example 1, except that the concentration of the 2.15L nickel sulfate solution pumped in step 1) is replaced with 0.04mol / L. The composition of the core of the Prussian white material is Na 1.543 Mn[Fe(CN)6] 0.907 1.57H2O, the composition of the first shell is Na 1.687 Mn 0.991 Ni 0.009 [Fe(CN)6] 0.922 1.46H2O, the composition of the second shell is Na 1.401 Ni[Fe(CN)6] 0.96 ·1.12H2O.

[0137] Comparative Example 1

[0138] This comparative example provides a Prussian white material, and its preparation method is basically the same as that of Example 1, except that the reaction is stopped after the first aging for 8 hours, the material is filtered and dried at room temperature to obtain the Prussian white material.

[0139] Comparative Example 2

[0140] This comparative example provides a Prussian white material, and its preparation method is basically the same as that of Example 1, except that after the first aging for 8 hours, 2.15L of 0.028 mol / L nickel sulfate solution is pumped in for a second aging for 8 hours, and the material is filtered and dried at room temperature to obtain the Prussian white material.

[0141] Comparative Example 3

[0142] This comparative example provides a Prussian white material, and its preparation method comprises the following steps:

[0143] 1) Under a nitrogen atmosphere, 15 L of a mixed solution of 1 mol / L manganese sulfate solution and 0.5 mol / L sodium ferrocyanide was pumped into 10 L of a base solution containing 0.1 mol / L sodium sulfate and 0.002 mol / L sodium ferrocyanide at a rate of 1.875 L / h, and stirred at a constant temperature of 25°C for 8 h; then the temperature was raised to 55°C and the mixture was aged for 8 h at a stirring rate of 300 rpm to obtain an aged solution.

[0144] 2) filtering the aged solution to obtain a Prussian white material precursor, drying the precursor at 80°C for 24 hours, and then vacuum drying the precursor at 180°C for 24 hours, and finally raising the temperature to 240°C for vacuum calcination for 0.5 hours to obtain a Prussian white material;

[0145] During the vacuum drying process, nitrogen was added every 30 min and the vacuum was drawn again.

[0146] Test Case

[0147] 1. The following parameters were tested on the Prussian white materials prepared in the above examples and comparative examples:

[0148] 1. Appearance observation

[0149] Figure 1 3 are appearance comparison diagrams of the Prussian white materials of Examples 1 to 6, wherein a and b are appearance diagrams of the Prussian white positive electrode materials of Examples 5 and 6, respectively. The materials of Examples 5 and 6 are yellow in color and have serious agglomeration, indicating that serious micro-oxidation has occurred, while c, d, e, and f are appearance diagrams of the Prussian white positive electrode materials of Examples 1 to 4, respectively. The colors of Examples 1 to 4 are whitish, and the dispersion is good, without obvious agglomeration.

[0150] 2. SEM

[0151] Figure 2 The SEM comparison diagrams of the Prussian white materials of Examples 1 to 6, wherein a and b are the Prussian white materials of Examples 5 and 6, respectively, and c to f are the Prussian white materials of Examples 1 to 4, respectively. Figure 2 It can be seen that high-temperature micro-carbonization does not destroy the cubic morphology structure of Prussian white itself, and the outer layer has an extended morphology, corresponding to a multi-layer shell structure.

[0152] Figure 7 This is a SEM image of the Prussian white material of Example 11. Figure 7 It can be seen that the Ketjen black of Example 11 is dispersed on the surface of the Prussian white material, and the Prussian white material is not coated.

[0153] 3. EDS

[0154] Figure 3 This is the EDS comparison diagram of the Prussian white material of Example 5, that is, the element composition of the Prussian white material that has undergone different temperature changes. Figure 3 a, b, c, d in the figure are the element distributions of the materials after treatment at 120℃-12h, 170℃-12h, 230℃-1h (after treatment at 170℃-12h), and 230℃-2.5h (after treatment at 170℃-12h). It can be found that the mass ratio of carbon and nitrogen elements remains basically unchanged before 170℃, and only after high-temperature treatment at 230℃ does a significant difference appear, corresponding to the decomposition of Prussian white on the surface and the formation of an amorphous carbon layer.

[0155] 4. Specific surface area

[0156] Test method: obtained by BET method, the test results are shown in Table 1.

[0157] 5. Sodium ion diffusion coefficient

[0158] Test method: obtained through electrochemical GITT test, the test results are shown in Table 1.

[0159] 6. Impedance curve

[0160] Test method: The impedance curve of button cell is tested by electrochemical workstation.

[0161] Figure 4 This is a comparison chart of the impedance curves of button-type batteries assembled with Prussian white materials of Example 2, Example 3, Example 5, and Example 6. Figure 4 It can be analyzed that the amorphous carbon layer formed by carbonization is beneficial to the transmission of ions and improves the conductivity of the material, corresponding to Example 3 having the lowest battery impedance.

[0162] 7. XRD

[0163] Test method: Use X-ray diffractometer to test the XRD spectrum of the material. Figure 5 The XRD characteristic curve comparison diagram of the Prussian white material of Example 1 before and after coating the shell is shown in FIG. Figure 5 It can be analyzed that after being coated by the first and second layers of the nickel-containing shell, the original single peak corresponding to the pure Mn core gradually separates into a double peak of the Mn-Ni composite phase morphology.

[0164] 8. Core particle size, first shell thickness, second shell thickness, carbonized layer thickness: Field emission transmission electron microscopy (Talos F200X, Thermo Fisher Scientific, USA) was used to characterize the core particle size, first shell thickness, second shell thickness, and carbonized layer thickness. Anhydrous ethanol was used to disperse the powder sample, and the test acceleration voltage was 60 kV. The test results are shown in Table 1.

[0165] 9. Ni content, Mn content: After 200 cycles, the battery was disassembled, and the diaphragm and the surface of the positive and negative electrodes were washed with 50 ml of pure water. The washing liquid was filtered to remove the residue and then sent to ICP-MS for testing. The content of metal elements in the filtrate was tested. The test results are shown in Table 1.

[0166] 10. D50 particle size: The D50 particle size of the Prussian white material was tested using a laser particle size analyzer. The test results are shown in Table 1.

[0167] 11. Water content: The water content of Prussian white material was tested using a Karl-Heinz moisture tester. The test results are shown in Table 1.

[0168] 12. C element and N element: C element is mainly tested by carbon sulfur instrument, and N element is calculated by EDS and chemical composition ratio.

[0169] 2. The Prussian white positive electrode materials of the above embodiments and comparative examples were assembled into button cells. The specific method was as follows: Prussian white: conductive carbon: PVDF = 86:7:7 mass ratio was mixed and NMP was added to form a slurry, which was evenly coated on aluminum foil, dried at 120 ° C for 12 hours, and then cut into 1.131 cm 2 The button cell was assembled using the sodium sheet as the counter electrode.

[0170] The button cell was tested for the following properties:

[0171] 1. Rate performance

[0172] Test method: The button cells assembled with the Prussian white positive electrode materials of the above examples and comparative examples were subjected to charge and discharge tests at currents of 0.1, 0.2, 0.5, 1, and 2C (1C = 150 mAh / g). The test results are shown in Table 1.

[0173] Figure 6The figure is a comparison chart of the rate performance of button cells assembled from the Prussian white materials of Examples 1 to 6. Figure 6 It can be seen that Example 3 after micro-carbonization coating has the highest capacity at different current densities, and the capacity decay is the slowest at different current ratios.

[0174] 2. Cycle performance: At 25°C, charge to 4.25V at a constant current rate of 1C, charge to 0.5C at a constant voltage rate of 4.25V, and then discharge to 2V at a discharge rate of 1C. Repeat this charge and discharge cycle 200 times, and measure the discharge capacity Q1 at the first cycle and the discharge capacity Q at the 200th cycle. 200 The capacity retention rate after 200 cycles is Q=Q 200 / Q1*100%.

[0175] 3. Specific capacity: At 25°C, charge the battery to 4.25V at a constant current of 1C, then charge it at a constant voltage of 4.25V to a current rate of 0.1C. The charging capacity at this time is recorded as the first-cycle charging specific capacity. After that, let it stand for 5 minutes, and then discharge it at a constant current of 1C to a voltage of 2V. The discharge capacity this time is recorded as the first-cycle discharge specific capacity of the battery.

[0176] Table 1

[0177]

[0178] The following conclusions can be drawn from Table 1:

[0179] The present invention coats a first shell of nickel-manganese-based Prussian white (Mn-NiHCF) on the surface of a pure manganese Prussian white (MnHCF) core, wherein the first shell is doped with nickel elements in the manganese-based Prussian white material, which can stabilize the crystal structure of the Prussian white material and thus inhibit the occurrence of the Jan-Taylor phenomenon, enhance the overall stability of the material, and enable the material to have both high capacity and excellent cycle stability.

[0180] Finally, it should be noted that those skilled in the art will readily conceive of other embodiments of the present invention after considering the specification and practicing the invention disclosed herein. The present invention is intended to cover any variations, uses or adaptations of the present invention, which follow the general principles of the present invention and include common knowledge or customary technical means in the art not disclosed by the present invention, are not limited to the precise structure described above and shown in the drawings, and may be modified and changed in various ways without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.

Claims

1. A Prussian white material, characterized in that: The Prussian white material comprises a core and a first shell coated on the surface of the core; The composition of the core is Na x Mn[Fe(CN)6] y αH2O, Among them, 1≤x≤1.8, 0.9≤y≤0.99, 0.5≤α≤3; The composition of the first shell is Na a Mn b Ni 1-b [Fe(CN)6] c βH2O, where 1.2≤a≤1.8, 0.8≤b≤0.995, 0.8≤c≤0.99, 0.5≤β≤3.

2. The Prussian white material according to claim 1, characterized in that: The particle size of the inner core is 1-6 μm; and / or the thickness of the first outer shell is 1-2 μm.

3. The Prussian white material according to claim 1, characterized in that: The surface of the first shell is also covered with a second shell, and the composition of the second shell is Na m Ni[Fe(CN)6] n γH2O, where 0.5≤m≤1.9, 0.9≤n≤0.99, 0.05≤γ≤1.

5.

4. The Prussian white material according to claim 3, characterized in that: The thickness of the second shell is 50-100 nm.

5. The Prussian white material according to claim 4, characterized in that The outer surface of the Prussian white material is a carbonized layer.

6. The Prussian white material according to claim 5, characterized in that: The thickness of the carbonized layer is 2-15 nm.

7. The Prussian white material according to claim 5 or 6, characterized in that: The Prussian white material includes the first shell and a carbonized layer located on the surface of the first shell, wherein the carbonized layer is formed by in-situ carbonization of the first shell; Alternatively, the Prussian white material includes the second shell and a carbonized layer located on a surface of the second shell, wherein the carbonized layer is formed by in-situ carbonizing the second shell.

8. The Prussian white material according to claim 7, characterized in that The in-situ carbonization includes: forced air drying at 60-100° C. for 4-24 hours, vacuum drying at 120-200° C. for 16-24 hours, and finally vacuum calcination at 205-240° C. for 0.5-5 hours.

9. The Prussian white material according to claim 1, characterized in that: The Ni content in the Prussian white material is 2000-10000 ppm, and the Mn content is 15-30 wt %.

10. The Prussian white material according to claim 1, characterized in that The Prussian white material satisfies at least one of the following conditions: (1) Specific surface area ≥ 4.5m 2 / g; (2) Sodium ion diffusion coefficient ≥ 1.14×10 -10 ; (3) D50 particle size is 2~10μm; (4) The difference in mass content between carbon and nitrogen is 0.5%~9.5%; (5) Water content ≤1200ppm.

11. A method for preparing the Prussian white material according to any one of claims 1 to 10, characterized in that: The following steps are involved: 1) adding a mixed solution of a soluble divalent manganese salt and sodium ferrocyanide to a mixed solution of a soluble sodium salt and sodium ferrocyanide at a rate of 1-2 L / h to perform a first coprecipitation reaction to obtain a first solution including a core; 2) adding a mixed solution of a soluble divalent manganese salt, a soluble divalent nickel salt and sodium ferrocyanide to the first solution to perform a second coprecipitation reaction to form a first shell on the surface of the inner core to obtain the Prussian white material.

12. The preparation method according to claim 11, characterized in that: After the first shell is formed on the surface of the inner core, the method further includes adding an aqueous solution of a soluble divalent nickel salt to the reaction solution to perform a third coprecipitation reaction to form a second shell and obtain the Prussian white material.

13. The preparation method according to claim 12, characterized in that: After forming the first shell or the second shell, the method further includes drying the material by forced air at 60-100°C for 4-24 hours, then vacuum drying the material at 120-200°C for 16-24 hours, and finally vacuum calcining the material at 205-240°C for 0.5-5 hours to form a carbonized layer on the surface of the Prussian white material.

14. A positive electrode sheet, characterized in that: The invention comprises a positive electrode current collector and a positive electrode active material layer, wherein the positive electrode active material layer comprises the Prussian white material according to any one of claims 1 to 10.

15. A battery, characterized in that: Including the positive electrode sheet as described in claim 14.

16. An electrical equipment, characterized in that: Comprising the battery of claim 15.

Citation Information

Patent Citations

  • Prussian blue type composite silicon negative electrode material and preparation method therefor

    CN107317002A

  • Gradient-structure Prussian white material and preparation method thereof, positive electrode material and sodium ion battery

    CN115966689A

  • Prussian blue sodium ion battery positive electrode material, preparation method and sodium battery

    CN116525795A

  • Prussian blue derived iron fluoride-carbon composite material, preparation method and application

    CN117902633A

  • Preparation method of composite Prussian blue sodium ion battery positive electrode material

    CN119219029A